Analysis Study of the "Tracing the Dots" Method in IMLA Learning for Students Ma'had Al-Izzah Leadership School Batu - Miftahul Hadi; Umi Machmudah; Nurhadi (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
The purpose of this research is to find out the imla' material and the imla' learning process using Tracing the Dots, as well as the benefits of using this theory in overcoming problems that occur. This research was carried out because it departed from the problem of new students who could not write Arabic, while this material was the basic material for mastering maharah kitabah. Many of them made the wrong choice of letters when dictated and could not tell which letters were connected and which were not. This research is qualitative field research with a case study type. Methods of data collection by observing and interviewing. Technical data analysis in the form of data reduction, data display, and conclusion. The results of this study explain that the process of teaching imla' at Ma'had Al-Izzah consists of 3 processes, namely letter recognition, connecting letters, and practicing Arabic writing. The material is taught by asking students to make the dotted line thicker so they practice a lot and get used to writing. With lots of practice, students learn without being burdened. They can also practice without being supervised by the teacher because the instructions and instructions are clear.